Frequency of Neonatal Sepsis in Babies Born to Mothers with Prom More Than 18 Hours - Sania Altaf, Muba Tahir, Madiha Javed, Nighat Afroz, Abdul Rauf Subhani, Ali Shan Liaqat (Pakistan Journal of Medical & Health Sciences, 2023)
PROM has a major impact on neonatal difficulties and sequelae in neonates who survive, in addition to perinatal morbidity and mortality. The purpose of this study was to ascertain how frequently babies born to moms who had PROM for longer than 18 hours experienced neonatal sepsis. The study was designed as a cross section. The study was carried out at the NICU, OPD, and Well Baby Nursery at the Shifa International Hospital in Islamabad. Assuming verbal consent, data was prospectively collected from patients. The study comprised 260 newborns in total who met the inclusion and exclusion standards. In our study, the mean gestational age, PROM duration, and weight were 38.723.24 weeks, 19.963.24 hours, and 2.861.12 kg, respectively. Of the 260 patients, 38 (14.6%) and 222 (85.4%) developed neonatal sepsis, respectively. Our findings imply that an identified risk factor for culture-proven newborn sepsis is premature membrane rupture > 18 hours. Such methods would be a safe and effective plan, especially in undeveloped countries. Keywords: Premature rupture of membrane, neonatal sepsis, morbidity and mortality.